Pressure induced phase transitions in copper (I) oxide and copper (II) oxide. - Legault, Richard. (University of Ottawa (Canada), 1995)
We have studied samples of CuO and Cu$\sb2$O to pressures of 60 GPa and 35 GPa, respectively, using energy dispersive X-ray diffraction. Samples were studied using a gasketed diamond anvil cell, energy dispersive X-ray diffraction at the Cornell High Energy Synchrotron Source, with a Mo or Al$\sb2$O$\sb3$:Cr$\sp{3+}$ pressure gauge. In the case of Cu$\sb2$O, the two phase transitions, (cubic to hexagonal to another hexagonal) as expected were seen. In CuO no definite phase transition was seen, although indications are given for CuO at 60 GPa converting to a distorted rocksalt-type structure from the initial monoclinic structure. The volume data obtained from the pressure experiments on CuO were best fitted with the third-order Birch-Murnaghan equation of state with B$\sb0$ = 110 GPa and B$\sb0\sp\prime$ = 5.5.
Keywords: Physics, Condensed Matter.